Disparitas Putusan Pidana Terhadap Pelaku Penelantaran Rumah Tangga Berdasarkan Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga Di Kota Pekanbaru.” - Prestasi Praja; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The criminal acts within the scope of household neglect criminal offense of domestic violence is classified as psychological domestic violence that can lead to mental burden for victims of perpetrators of domestic violence. Domestic violence belong to a specific criminal offense. In the High Court there are disparities Pekanbaru 3 criminal assault household negligence. First, the decision No. 219 / pid.sus / 2013 / ptr, Second, decision No. 45 / pid.sus / 2014 / ptr, Third, decision No. 150 / pid.sus / 2016 / pt.pbr.Based on the description in the background of the above problems, then formulate the problem as follows: First, Do the factors that cause the disparity perpetrators of neglect of household decision based on Law No. 23 of 2004 on the elimination of domestic violence in the city of Pekanbaru ?. Second, whether the judge has been performing its role in accordance with fairness, certainty and effectiveness in deciding criminal assault household negligence in Pekanbaru?.This type of research is classified dala kind of normative legal research. Penellitian type is descriptive analysis. The data used was obtained through three (3) legal materials is the primary legal materials, secondary, and tertiary. The data collection techniques were performed using methods, namely the study of literature.From the results of research and discussion can be concluded that the First, the main factors being 3 An appeal disparities in the criminal act of neglect of households in the High Court Pekanbaru are: problems of philosophy; sentencing guidelines; criminal benchmark issues; factor that comes from self-judge alone. Second, the judge has been carrying out its role in accordance with certainty in deciding criminal assault household negligence In the city of Pekanbaru. But viewed from the aspect of justice and expediency judges not done it, can be seen from the 3 three decision in the District Court Rengat and Pekanbaru an appeal, in because the defendant does not feel fair share of the verdict. Suggestions in this study is the first, then to minimize the negative impact of the disparity of criminal needs be a rule or rules which can be a guide judges in the administration of the criminal verdict to the defendant. Second, Providing information that is very clear to the public on the causes of the disparity criminal, the cases that concern people who are indirectly giving legal education to society should need to be improved to increase public knowledge about the judicial process and the law itself.Keywords: Disparity - Decision - Criminal Act - Domestic Neglect